Kandungan Fluoride pada Ikan Teri (Stolephorus commersonnii) dan Potensinya dalam Pencegahan Karies Gigi - Mutiara Dewi Pangaribuan; Sondang Pintauli; Saharman Gea (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Dental caries is a common infectious disease that leads to the demineralization and structural degradation of the tooth's hard tissues, caused by acid-producing bacteria such as S. mutans through carbohydrate fermentation. One of the essential strategies for caries prevention is using fluoride to inhibit bacterial activity and enhance enamel remineralization. Anchovy Stolephorus commersonnii, widely found in Indonesian waters, were rich in calcium and fluoride, particularly in the form of calcium fluoride (CaF₂), which may offer potential benefits in preventing dental caries. Objective: This study aimed to assess the fluoride concentration in S. commersonnii nanopowder to evaluate its potential as a natural source of fluoride for dental caries prevention. Materials and Methods: This research was a descriptive laboratory-based experimental study. The sample was Stolephorus commersonnii (S. commersonnii). The sample was prepared through drying, acid maceration, and high-energy milling to produce nanoparticle powder. Fluoride content was measured using two methods: a colorimetric method with a spectrophotometer and a portable fluoridemeter based on the SPADNS method. Results: The results showed that the fluoride concentration was 21.05 mg/100 g (21.05 ppm) by spectrophotometry and 20.0 ppm using the SPADNS method. The S. commersonnii nanopowder contained 1,305.80 mg/100 g calcium, 281.60 mg/100 g phosphorus, and 91.5% of particles were in the nano size. Conclusion: S. commersonnii nanopowder contains a considerable amount of fluoride and minerals, suggesting its potential as a natural dietary source of fluoride in supporting dental caries prevention strategies.